Efektifitas Penggunaan Quick Response Code Indonesian Standard (QRIS) untuk Meningkatkan Omset Penjualan pada UMKM di Bandar Lampung (Studi Kasus Kl Cofee Bandar Lampung, Kopi Ketje Kedaton dan Marley’s Cafe) - Novita Christine; Khairudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aimed to test the effectiveness of using the Indonesian Quick Response Code (QRIS) standard to increase revenue in three small and medium enterprises, KL Coffe, Kopi Ketjeh and Marley's Kedaton in Bandar Lampung City. This study uses a qualitative approach using the theory of planned behavior as a basis for formulating interview questions and data analysis. Data was collected through in-depth interviews with three relevant business actors (MSMEs). The data were then analyzed using descriptive analysis. The results showed that the use of the Indonesian Standard Quick Response Code (QRIS) significantly increased the revenue of the studied SMEs.